1983
DOI: 10.1172/jci110878
|View full text |Cite
|
Sign up to set email alerts
|

Modification of chemically induced diabetes in rats by vitamin E. Supplementation minimizes and depletion enhances development of diabetes.

Abstract: A B S T R A C T Administration of the antioxidant vitamin E to rats, prior to administration of either streptozotocin or alloxan, provided protection against the diabetogenic effect of both these agents. This was demonstrated by their response to a glucose load, their pancreatic insulin content and light microscopy findings. In addition, rats whose antioxidant state was depleted, by being maintained on a vitamin E and selenium-deficient diet, demonstrated increased diabetogenic susceptibility to normally nondi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
1

Year Published

1985
1985
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(20 citation statements)
references
References 21 publications
2
16
0
1
Order By: Relevance
“…Our results add strength to the hypothesis, supported by animal experiments, that a sufficient intake of antioxidants plays a role in type 2 diabetes prevention (27,28). The results corroborate findings in earlier prospective studies, suggesting an inverse association between serum levels of total vitamin E, ␣-tocopherol, and incidence of type 2 diabetes (4,6).…”
Section: Methodssupporting
confidence: 90%
“…Our results add strength to the hypothesis, supported by animal experiments, that a sufficient intake of antioxidants plays a role in type 2 diabetes prevention (27,28). The results corroborate findings in earlier prospective studies, suggesting an inverse association between serum levels of total vitamin E, ␣-tocopherol, and incidence of type 2 diabetes (4,6).…”
Section: Methodssupporting
confidence: 90%
“…Diabetes is a disease characterized by increased oxidative stress, as indicated by elevated concentrations of lipid peroxidation products in the plasma. 35) Slonim et al,8) demonstrated that administration of vitamin E to rats provided protection against the diabetogenic action of alloxan. Dillard et al,36) demonstrated that in vitamin E deficient rats alloxan induced an increase in levels of pentane and ethane in the expired breath and thiobarbituric acid reactive substances (TBARS) in plasma, liver and pancreas.…”
Section: Discussionmentioning
confidence: 99%
“…The alloxan toxicity has been attributed to its direct interactions with islet protein kinase (41) and to its well-known ability to generate highly reactive oxygen radicals (42,43). It is not yet clear whether the destructive effects of streptozotocin are also elicited by free radicals or whether they develop after alkylation of DNA bases (44)(45)(46)(47)(48)(49). Differences in protective conditions have often been considered as arguments in favor of a different action mechanism ofthe two diabetogenic compounds.…”
Section: Four Different Conditions Leading To B-cell Death In Vitromentioning
confidence: 99%